The therapeutic potential of exosomes in immunotherapy - Li, Guangyao; Zhang, Shuyi; Zou, Yitan; Ai, Hongru; Zheng, Xinya; Qian, Kewen; Lei, Changhai; Fu, Wenyan (Frontiers in Immunology, 2024)
Exosomes are found in various tissues of the body and carry abundant contents including nucleic acids, proteins, and metabolites, which continuously flow between cells of various tissues and mediate important intercellular communication. In addition, exosomes from different cellular sources possess different physiopathological immunomodulatory effects, which are closely related to the immune regeneration of normal or abnormal organs and tissues. Here, we focus on the mechanistic interactions between exosomes and the human immune system, introduce the immuno-regenerative therapeutic potential of exosomes in common clinical immune-related diseases, such as infectious diseases, autoimmune diseases, and tumors, and reveal the safety and efficacy of exosomes as a novel cell-free immune regenerative therapy.